Association of Preoperative HbA1c Level with Incidence of New-onset Atrial Fibrillation during Early Postoperative Period after Off-Pump Coronary Artery Bypass Grafting Surgery in Diabetic Patients (Cardiovascular Journal, 2020)
Background: Diabetes mellitus is an independent risk factor for coronary artery disease and it adversely affects the postoperative outcome after CABG surgery. Adequate control of diabetes for a longer period, which can be assessed by HbA1c, before OPCAB may reduce development of postoperative atrial fibrillation and thus improve outcome.Methods: This was an observational study included sixty diabetic patients purposively who underwent isolated off pump coronary artery bypass procedure in NICVD. Total sample contained 60 diabetic patients, which were divided in two equal groups. Grouping was Group I – 30 Diabetic patients with preoperative HbA1c